Type 2 diabetic patient with a foot ulcer as initial manifestation of diffuse large B-cell lymphoma: A case report. (May 2016) - Iacopi, Elisabetta; Coppelli, Alberto; Goretti, Chiara; Loggini, Barbara; Piaggesi, Alberto
Highlights: Foot complications are frequent in patients with diabetes and represent a major cause of hospitalization and amputation in western Countries. With increase of life expectancy, in people with diabetes it is not uncommon to find chronic wounds due to pathogenic mechanisms different from diabetes. Clinicians who are managing a chronic foot ulcer in diabetic patient should consider pathogenic mechanisms alternative to diabetes and its complications when the ulcer is unresponsive to usual medical treatment. Abstract: Diabetic foot ulcerations (DFU) represent a major cause of hospitalization and amputation. In people with diabetes it's not uncommon to find chronic wounds due to pathogenic mechanisms different from diabetes. Here we report the case of a foot lesion misdiagnosed as DFU but actually caused by diffuse large B-cell lymphoma.